Diversity and Succession of Actinobacteria in the Forelands of the Tianshan Glacier, China. Issue 8 (13th September 2016) - Zhang, Binglin; Wu, Xiukun; Zhang, Wei; Chen, Ximing; Zhang, Gaosen; Ai, Xue; Sun, Likun; Zhang, Baogui; Liu, Guangxiu; Chen, Tuo; Dyson, Paul
ABSTRACT: Actinobacteria are typically soil bacteria that have important roles in soil development and biogeochemical cycling. However, little is known about the occurrence or the succession of communities of Actinobacteria in new habitats. In this study, we investigated the diversity and succession of the actinobacterial communities that inhabited the forelands of the Tianshan Glacier (China), which ranged in successional age from 0 to 100 years since the forefield was deglaciated. Actinobacteria was one of the dominant phyla in the glacier foreland and included the orders Acidimicrobiales, Actinomycetales, Rubrobacteriales and Solirubrobacteriales. Actinomycetales was the dominant order, but its relative abundance decreased through the chronosequence. Acidimicrobiales and Solirubrobacteriales were more abundant in the late stages of succession than in the early ones. The abundance of Rubrobacteriales was only high at 74a. The dominant genera Nocardioides and Arthrobacter were widely distributed and were found in each stage of succession. With nonparametric and rarefaction estimated analyses, we found that the phylotype richness of Actinobacteria was significantly correlated with time ( r = 0.886, p = 0.019). The succession of actinobacterial communities was divided into 3 stages: the early stage (6a), the intermediate stage (10a and 20a) and the late stage (60a, 74a, and 100a). Based on the canonical correspondence analysis, the actinobacterial communities were affected significantly by soil pH ( r = −0.834, p = 0.039) and somewhat by the C/N ratio ( r = 0.783, p = 0.066). The nonmetric multidimensional scaling analysis showed that the effect of geographical isolation on the actinobacterial communities was greater than that of the soils in the development of the chronosequence.